A simplified two-dimensional culture system supports meiotic progression during mouse spermatogenesis in vitro - Yuki Yokoi; Yuki Yamashita; Koichi Uemura; Hisakazu Odaka; Kazuhide Makiyama; Takehiko Ogawa; Takuya Sato; Mitsuru Komeya (PLoS ONE, 2026)
In vitro spermatogenesis (IVS) remains a major challenge due to its complexity and extended duration. Although organ culture of neonatal mouse testes can support complete spermatogenesis, its three-dimensional structure limits precise observation and control of culture conditions, resulting in heterogeneous oxygen and nutrient gradients. Two-dimensional (2-D) systems provide greater accessibility but often induce accelerated or abnormal meiosis. In this study, we present a simplified, serum free 2-D culture system that enables meiotic progression of mouse germ cells to the mid pachytene stage. Testicular cells from Acrosin ( Acr )-GFP transgenic mice (2.5 to 10.5 days postpartum : dpp) were enzymatically dissociated and cultured in APEL medium, a chemically defined and serum free basal formulation. The medium was supplemented with bovine pituitary extract (BPE), follicle stimulating hormone (FSH), and testosterone (BFT medium). Meiotic progression was monitored in real time by GFP fluorescence and further assessed by immunocytochemistry and nuclear spread analysis. Testicular cells consistently formed Sertoli cell monolayers and supported germ cell differentiation to mid pachytene stage. GFP-positive cells appeared around days 17.5 to 21.5 of culture, reflecting a modest delay compared to organ culture. GFP-positive cells were observed not only in 7.5 to 10.5 dpp cultures, but also in 2.5 to 6.5 dpp testes lacking preexisting spermatocytes, indicating de novo induction of meiosis. BFT medium, compared to APEL medium, increased the frequency of GFP-positive wells and the per-well duration of GFP expression, reaching statistical significance in the 9.5–10.5 dpp group (p = 0.021). Nuclear spread analysis confirmed synapsis through pachytene, although cells did not progress to diplotene. This simplified culture system offers a robust and accessible platform for studying early meiotic events and optimizing IVS.